EP1287 A unique case report: postoperative palmar digital thrombophlebitis in a young primer Sjögren's syndrome patient with high grade serous ovarian cancer. (1st November 2019) - Keles, E; Kabaca Kocakuşak, C; Çelik, Z
Abstract : Introduction/Background: Sjögren´s Syndrome (SjS) is a chronic autoimmune inflammatory disease of unknown etiopathology, characterized by focal lymphocytic infiltration of the exocrine glands (predominantly lacrimal and salivary glands), mainly affects middle-aged women. SjS have an increased risk of developing malignant neoplasm, particularly non-Hodgkin lymphoma.SjS carries an elevated risk of deep vein thrombosis (DVT) and pulmonary embolism (PE). Methodology: While (SjS) mostly affects patients in between the fourth and sixth decade of life, a young SjS patient is a rare event. Additionally the patient diagnosed with high grade ovarian cancer is an uncommon phenomenon, judging by scarcity of published data. Results: What makes our case unique is ; there is a paucity of data on postoperatively palmar digital thrombophlebitis which seen infrequently.We present a 35 year SjS patient with high grade serous ovarian cancer; postoperatively developed pneumothorax in right lung and atelectasıa with effusion ın left lung concomitant with thrombophlebitis in the 5th finger. Conclusion: Herein, we report a unique case report: Postoperative palmar digital thrombophlebitis in a young primer Sjögren's Syndrome patient with high grade serous ovarian cancer. Disclosure: Nothing to disclose